SISTEM PENCARIAN LOKASI ANJUNGAN TUNAI MANDIRI (ATM) MEMANFAATKAN GOOGLE MAP UNTUK HANDPHONE ANDROID YANG MEMILIKI FASILITAS GLOBAL POSITIONING SYSTEM (GPS) STUDI KASUS BPD DIY - Nurahmanto, Hendra; Sumarsono, Sumarsono; Suhayati, Maya (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
The denser the activity o f modern lifesquad, made in every case the limitations o f everyday life. As an example when the transactions at the Bank, this can be facilitated by the presenc o f ATM. Meanwhile, many users do not know ATM locations, especially when users from the other town so it is considered sufficient applied for search ATM locations. The method used in this study for mapping utilizing google map. In this application user can search for ATM locations easily as determined by the position o f the user is located. With GPS devices available on the smartphone can find locations user smartphone and ATM locations. ATM search applications can be used when the smartphone is connected to internet.